A research about data-driven simulation approach for Rolls-Royce 150 seater engine supply chain - Shi, Shuaijie (2007)
This dissertation is about a data-driven simulation applied on the supply chain improvement project for Rolls-Royce. Rolls-Royce is now planning design an engine for 150 seats Boeing 737. One of requirements of Boeing is less than 65 days lead time. Compared current 2 years lead time, it is a big challenge for Rolls-Royce's supply chain. A data-driven simulation method is applied in this article to solve this problem. The model of 150 seater engine supply chain is built by data-driven simulation. Supply chain theories are used to analyze the model and provide solutions. Data-driven simulation experiment one of the solutions in supply chain model. At last, recommendation is given in last chapter.